PERFORMANCE OF DIESEL ENGINE WITH EGR SYSTEM - Ravindra Sadashiv Deashpande; Sohail Bux; A.C Tiwari (International Journal of Innovations in Engineering Research and Technology, 2021)
Reducing NOx emission in a diesel engine is a major issue for its environmentally harmful influences. To cope with the problem, the current diesel engine is equipped with EGR. Actually, it is known that EGR can help to reduce NOx emission by limiting oxygen supplied into intake manifold, lowering the combustion temperature. However, it also reduces engine performance. In the present investigation is carried out to study the effect of the Exhaust Gas Recirculation (EGR) on the performance and emission characteristics of the C.I. engines. To overcome the problem of NOx formation in the CI engine due to higher temperature the part of exhaust gases are recirculated to the engine cylinder. The EGR rate is varied in the engine I the proportion from 0%, 5%, 10 % and 15%. One set of experiment is conducted for each EGR rate, for studying the performance & emission characteristics of the engine. Then the performances and emissions characteristic for EGR rates were studied and results were compared with the performance and emission characteristics of without EGR.